Synthesis, Antimicrobial, and Computational Evaluation of Novel Isobutylchalcones as Antimicrobial Agents. (26th December 2017) - Shaik, Afzal Basha; Yejella, Rajendra Prasad; Shaik, Shahanaaz
Abstract : A series of 25 new chalcones were synthesized by Claisen-Schmidt condensation, well characterized by spectroscopic data, and evaluated for their antibacterial and antifungal activities by serial tube dilution method. Among the compounds tested, A3 andA6 containing 2, 4-dichlorophenyl and 2, 4-difluorophenyl moiety, respectively, were found to be the most potent in the series against both bacterial and fungal strains with a MIC value of 16 µ g/mL in each case. Further computational evaluation for antimicrobial activity was performed by atom based 3D-QSAR using PHASE™ software in order to have a correlation between the observed activities and predicted activities. The computational studies were in agreement with the in vitro antimicrobial results and had identified the most promising chalcones as antimicrobial agents and the responsible structural features for the proposed activity.